Aplicación del programa de estimulación “Niños felices”basado en el constructivismo para favorecer el desarrollo de la lecto escritura en niños/as de 5 años de I.E.I N°314 “Sector Rupacucha” - Pérez Echeverría, Marco Jorge Luis (2014)
This research was conducted at the Center for Research, Education and Agroforestry Production, located in the city of Yurimaguas, in the department of Loreto. Here , 06 aboveground biomass was determined agroforestry systems : Simarouba love "marup" 2 years of establishment; Swietenia macrophylla "mahogany", established 6 years; Simarouba love "marupa", 2 years of established and Swietenia macrophylla "mahogany" 6 years established ; Simarouba love "marupa" and Swietenia macrophylla "mahogany ", 5 years established ; Calycophyllum spruceanum "Capirona" and Myroxylon balsamum "storax", 5 years of established and " Calycophyllum spruceanum "Capirona" 6 years of established and Citrius limom " lemon " , 10 years of establishment. The methodology was developed by Alegre et all to similar conditions, comprising: measuring tree diameters at breast height to calculate the volume of trees, so that finally, the carbon is calculated in these agroforestry systems. At the end of the whole process of investigation reached the following conclusions: 1) The treatment T4 (Marupa - mahogany - 5 years) scored the highest average diameter at breast height with 8.87 cm statistically outperforming the averages obtained by the treatments T2 (T2 : Mahogany - 6 years) T5 (Capirona - estoraque - 5 years) , T1 (Marupa - 2 years) , T6 (Capirona - lemon) and T3 (Marupa - mahogany - 6 years) who reported averages 5.98 cm, 5.88 cm , 5.21 cm 5.19 cm and 5.10 cm in diameter at breast height respectively. 2) The treatment T4 (Marupa - mahogany - 5 years) had the highest average Kg / tree C with 20.32 kg / tree C statistically outperforming the averages obtained by treatments T5 ( Capirona - estoraque - 5 years) , T2 (T2 : Mahogany - 6 years), T3 ( Marupa - mahogany - 6 years) , T6 (Capirona - lemon) , T1 (Marupa - 2 years) , and who reported averages of 6.12 Kg / tree 5.1 kg / tree , 4.85 kg / tree , 4.02 kg / tree and 3.69 kg / tree respectively . 3) T4 (Marupa - mahogany Treatment - 5 years) had the highest average of 33.5 C -1 Tn.ha statistically outperforming the averages obtained by treatments T5 ( Capirona - estoraque - 5 years ) , T2 (T2 : mahogany - 6 years), T3 ( Marupa - mahogany - 6 years) , T6 ( Capirona - lemon) , T1 ( Marupa - 2 years ) , and who reported averages 10.19 Tn.ha -1, 8,5 Tn . ha-1 , 8.09 Tn.ha -1 , 6.69 and 6.14 Tn.ha Tn.ha -1 C -1 respectively